Pengaruh Kualitas Pelayanan Dan Suasana Toko Terhadap Kepuasan Konsumen Pada Business Centre SMKN 1 Lemahabang Cirebon - Isti Riana Dewi (Jurnal Ilmiah Ekonomi Bisnis, 2021)
The purpose of this research was to find out the influence between service quality and the atmosphere of the store on customer satisfaction at the Business Center at a vocational high school in Lemahabang Cirebon. Research methods used are validity test, reliability test, and Multiple Linear Regression. The analysis technique used is multiple linear regression. The results of this study explain the influence between service quality of the store and the atmosphere of the store on customer satisfaction. This indicates that there needs to be an improvement of services such as honest words and friendly behavior to improve the quality of store service and modify the temperature and layout of goods to be more varied to entice customers to feel happy and make more visits to support the success of the business.